SYLLOGISTIC REASONING FROM PETRUS HISPANUS TO MODERN CONCEPTUALIZATIONS - TOMI, Paula Pompilia (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
This paper is going to present the syllogistic reasoning beginning with the Middle Ages and comparing the traditional type of this kind of reasoning with some modern conceptualizations (Hodges and Makinson). In this paper is emphasized the view of Petrus Hispanus, a Middle Age philosopher who based his point on Aristotle’s and Boethius’ logic. There is a difference between their presentations of this reasoning. The conceptual difference between Aristotle’s and the traditional one is going to be pointed. The problem of the fourth figure is also going to be considered. The conclusion of this analysis is going to underline the evolution and continuity of the syllogistic reasoning.